Best Practices in End of Life and Palliative Care in the Emergency Department - Prachanukool, Thidathit; George, Naomi; Bowman, Jason; Ito, Kaori; Ouchi, Kei (Clinics in geriatric medicine, 2023)
Three-quarters of patients over the age of 65 visit the emergency department (ED) in the last six months of their lives. Approximately 20% of hospice residents have ED visits. These patients must decide whether to receive emergency care that prioritizes life support, which may not achieve their desired outcomes and might even be futile. The patients in these end-of-life stages could benefit from early palliative care or hospice consultation before they present to the ED. Furthermore, early integration of palliative care at the time of ED visits is important in establishing the goals of the entire treatment.